METADISCOURSE MARKERS WRITTEN IN INTRODUCTION SECTION OF FINAL PROJECT OF UNIMUS EFL LEARNERS - Siti Aimah; Dodi Mulyadi; Muhimatul Ifadah (English Review: Journal of English Education, 2019)
Metadiscourse marker is one of determining indicators of the quality of the writers’ writing. Metadiscourse markers enable the writers to interact with the readers effectively. What commonly happens to many undergraduate students studying English as a foreign language is that they are not able to develop an engagement between themselves, their texts, and their readers. Thus, this study investigates the types of metadiscourse markers used by Unimus EFL learners in final project introduction sections, and markers that are frequently used by them in their writing. By using qualitative and quantitative research method, seven introduction sections of final project of Unimus EFL learners focusing on qualitative and qualitative research methods were chosen purposively. As result, the study revealed that in writing introduction sections, the students used various metadiscourse markers, including interactive resources (transitions, frame markers, endophoric markers, evidentials, and code glosses) and interactional resources (hedges, boosters, attitude markers, engagement markers, and self-mensions). Among those categories, interactive resources were found to be frequently used by the learners rather than interactional resources. It means that the writers tended to give attention to and guided the readers through the text by establishing their interpretations explicitly rather than involving the readers in the argument through the use of markers in interactional dimension.